“Sex” versus “Gender” in the Jurisprudence of the Constitutional Court (How the Lack of Feminist Legal Studies in Bulgaria Led to Distortion of the Basic Category of “Gender” in the Legal Discourse?) - Marcheva, Deyana (Yearbook of the Law Department, 2020)
The Bulgarian Constitutional Court (CC) finds it necessary to differentiate between the concept “sex” and the concept “gender” in the Istanbul Convention within its preliminary constitutional control. As the second one is fundamental for the convention and the CC sees a problem with it, the CC concludes that the convention is in contradiction with the Bulgarian Constitution. Furthermore, in November 2021 in an interpretation decision the CC states that the under the Constitution the Bulgarian concept relates only to the meaning of “sex”, in its biological meaning. The way in which the CC operates with the terms “sex” and “gender” brings to the fore serious deficits in Bulgarian legal discourse resulting from the total lack of any feminist jurisprudence and the isolation from the contemporary debates on the gender-based inequalities and injustices.